Clinical study on the feasibility of new thrombus markers in predicting massive cerebral infarction - Zhao, Xiaoxia; Yang, Siyu; Lei, Ruining; Duan, Qiaoyan; Li, Jundong; Meng, Jiangtao; Sun, Lei (Frontiers in Neurology, 2023)
Objective This study investigated the diagnostic performance of the thrombin-antithrombin complex (TAT), plasmin-α2 plasmin inhibitor complex (PIC), tissue plasminogen activator-plasminogen activator inhibitor complex (t-PAIC), and thrombomodulin (TM) in the early identification of massive cerebral infarction. Method A total of 423 patients with cerebral infarction confirmed by imaging examination were divided into the massive cerebral infarction (MCI) group and the non-massive cerebral infarction (NMCI) group. TAT, PIC, t-PAIC, and TM were measured immediately after admission. The diagnostic performance was analyzed by the receiver characteristic operating curve (ROC). Result The median plasma concentrations of TAT, PIC, and t-PAIC in patients with MCI at early onset were 5.10 ng/ml, 1.11 μg/ml, and 8.80 ng/ml, respectively, which were higher than those in patients with NMCI (2.20 ng/ml, 0.59 μg/ml, and 7.35 ng/ml), and the difference was statistically significant (P < 0.001). TAT was shown to be an independent risk factor for the development of massive cerebral infarction by a multivariate logistic regression analysis (OR = 1.138). A ROC curve analysis showed that PIC had the best performance in identifying MCI at an early stage (AUC = 82.8%), with a sensitivity of 80.7% and a specificity of 76.2% when the PIC concentration was ≥0.8 μg/ml; TAT had the highest specificity in identifying MCI, with a specificity of 80.6% when the TAT concentration was ≥3.97 ng/ml. Conclusion The detection of PIC, TAT, t-PAIC, and TM is a comprehensive assessment of vascular endothelial damage and activation of the coagulation and fibrinolytic systems and has diagnostic value for early identification of patients with MCI, which, together with its ease of detection, can be used as a plasma marker for early identification of large vessel occlusion.